2006
DOI: 10.1111/j.1365-2389.2006.00856.x
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved organic carbon interactions with sorption and leaching of diuron in organic‐amended soils

Abstract: Diuron (N¢-[3,4-dichlorophenyl]-N,N-dimethylurea) is one of the most frequently used herbicides in olive groves in Spain and other Mediterranean countries. The main objective of this work was to investigate the effect of the dissolved organic carbon (DOC) from a commercial humic amendment, derived by composting the liquid waste of the olive-mill process (LF), and a solid residue from the olive oil production industry (AL) on the sorption and leaching behaviour of diuron in soil. For this purpose, a clay and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 39 publications
6
30
0
1
Order By: Relevance
“…Firstly, organic pollutants can interact with DOM via hydrophobic interaction or complexation (Ilani et al 2005;Nelson et al 2000). Secondly, DOM can compete with organic pollutants for the sorption sites on the sorbent (Cox et al 2007). Additionally, DOM can be adsorbed to the sorbent first and then interact with the sorbate (Ling et al 2006;Sun et al 2008).…”
Section: Influence Of Dissolved Organic Mattermentioning
confidence: 99%
“…Firstly, organic pollutants can interact with DOM via hydrophobic interaction or complexation (Ilani et al 2005;Nelson et al 2000). Secondly, DOM can compete with organic pollutants for the sorption sites on the sorbent (Cox et al 2007). Additionally, DOM can be adsorbed to the sorbent first and then interact with the sorbate (Ling et al 2006;Sun et al 2008).…”
Section: Influence Of Dissolved Organic Mattermentioning
confidence: 99%
“…Several studies have demonstrated the beneficial effects of TPOMW in restoring crop productivity in degraded soils (López-Piñeiro et al, 2006, but very few studies have investigated diuron's behaviour in fresh TPOMW-amended soils Cox et al, 2007), and even fewer have been carried out in situ under field conditions, due to the high cost and difficulty (Cabrera et al, 2008a(Cabrera et al, ,b, 2009). In addition, to the best of our knowledge, there is no information on the influence of TPOMW organic matter transformation on diuron's fate in soils following repeated applications of this waste also under field conditions, although such information would be useful from the environmental perspective of the management of this herbicide in soils receiving this waste.…”
Section: Introductionmentioning
confidence: 98%
“…According to Tixier et al (2001), diuron can undergo transformations forming by-products with even greater toxicity. Its degradation in environment mainly occurs through microorganism biological activity, producing three primary metabolites: 3,4-dichlorophenylurea (DCPU), 3-(3,4-dichlorophenyl)-1-methylurea (DCPMU), and 3,4-dichloroaniline (DCA) (Dalton et al 1996, Cox et al 2007). These by-products can persist longer in aquatic and terrestrial ecosystems due to its great stability (Tixier et al 2000, Sorensen et al 2003.…”
mentioning
confidence: 99%